Hydroxybenzoic acid isomers and the cardiovascular system - Juurlink, Bernhard HJ (BioMed Central, 2014)
Today we are beginning to understand how phytochemicals can influence metabolism, cellular signaling and gene expression. The hydroxybenzoic acids are related to salicylic acid and salicin, the first compounds isolated that have a pharmacological activity. In this review we examine how a number of hydroxyphenolics have the potential to ameliorate cardiovascular problems related to aging such as hypertension, atherosclerosis and dyslipidemia. The compounds focused upon include 2,3-dihydroxybenzoic acid (Pyrocatechuic acid), 2,5-dihydroxybenzoic acid (Gentisic acid), 3,4-dihydroxybenzoic acid (Protocatechuic acid), 3,5-dihydroxybenzoic acid (α-Resorcylic acid) and 3-monohydroxybenzoic acid. The latter two compounds activate the hydroxycarboxylic acid receptors with a consequence there is a reduction in adipocyte lipolysis with potential improvements of blood lipid profiles. Several of the other compounds can activate the Nrf2 signaling pathway that increases the expression of antioxidant enzymes, thereby decreasing oxidative stress and associated problems such as endothelial dysfunction that leads to hypertension as well as decreasing generalized inflammation that can lead to problems such as atherosclerosis. It has been known for many years that increased consumption of fruits and vegetables promotes health. We are beginning to understand how specific phytochemicals are responsible for such therapeutic effects. Hippocrates’ dictum of ‘Let food be your medicine and medicine your food’ can now be experimentally tested and the results of such experiments will enhance the ability of nutritionists to devise specific health-promoting diets.